Making The Invisible Visible: A Phenomenological Exploration Of Teacher Experiences with Digital Simulations - Gemcer Selda; Princes Joy S Muyo; Princess Ann P Pelaez (RSF Press, 2026)
This study explores the personal experiences of elementary teachers using digital simulations to teach difficult science topics. Using a phenomenological approach, the research looks at how eight (8) science teachers make sense of their roles when using these digital tools. Through deep interviews, the study found that simulations are more than just tools; they change how teachers think about and plan their lessons. The findings show that simulations help teachers turn abstract ideas into